Epistemology Ta’wil: a Study of Hassan Hanafi’s Ideas in Interpreting Al-Qur’an - Taufiqurrahman, (QOF, 2023)
Hassan Hanafi was educated in a fundamentalist Islamic social environment, and then received Western scientific and methodological knowledge. The defeat of Egypt and Islam from Israel and the Egyptian atmosphere which was full of repressive and authoritarian actions, made him a figure who in his way of thinking wanted to find solutions for the development of Islam. One of them is the effort to interpret (ta’wīl) the Qur'an from the current perspective, especially in Egypt. This article will reveal the epistemology initiated by Hassan Hanafi in interpreting the Qur'an, by finding out the sources of interpretation, approaches, and applicative steps in interpreting it and the background. The results of the study found: 1) The source of Hassan Hanafi's interpretation of the Qur'an is taken from oral data and codified data in the form of text, which looks silent but alive, and when we read more will show various forms. 2) Hassan Hanafi's al-Qur'an interpretation approach is ushul fiqh, phenomenology, Marxism and Hermeneutics. 3) The step of interpretation by building a thematic interpretation, by making the problems that occur into the object, to produce the interpretation needed by the community as a solution for progress. From what was initiated by Hanafi, in essence much has been done by previous mufassir. But what makes it different is the situation he experienced made him build a social interpretation of Al-Qur'an, which is reformist, liberating and humanist.